Grammatical and Lexical Analysis of Dialects of Uzbek - Turaeva Dildora Anvarovna (International Journal Of Literature And Languages, 2025)
The article discusses the organization of the examination process for determining the grammatical and lexical characteristics of territorial words. On the basis of a number of methods in organizing the process of linguistic expertise of anonymous, problematic correspondence on social networks, it was thought about the emergence of conclusions and stops that are relevant for the judicial system. As a result of the tsuhuncha of contactology in Areal linguistics, it has been reported that the mixing of several sister languages and its occurrence of territorial specificity in speech.